Application of alpha-oxopropionic acid to perovskite active layer, perovskite solar cell module and preparation methods of alpha-oxopropionic acid and perovskite solar cell module
By introducing A-oxygenic acid organic molecule modifiers in the introduction of perovskite solar cells, modify the perovskite/metal oxide interface, solve the problem of energy loss caused by the defects of the perovskite film interface, improve the performance of photovoltaic and stability. sex.
Patent Information
- Application Number
- CN202411496070.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
There is a gap between the theoretical limit efficiency of perovskite solar cells and the actual situation. The main reason is that there are a large number of non-intrinsic defects at the interface and grain boundaries of perovskite films, which hinder carrier extraction and cause energy loss.
The introduction of organic molecular layers modify the interface of the perovskite/metal oxide electronic transmission layer, and use A-oxygen propionate as an organic molecular modification layer. The small molecular modification layer is formed by rotation and annealing treatment, reducing the non-radiation at the interface Compound loss.
Effectively reduce the non -radiation composite loss of photogonic loads at the interface, reduce the overall energy loss of the device, and improve the photovoltaic performance and atmospheric stability of solar cells.
Smart Images

Figure BDA0005101282190000191 
Figure HDA0005101282200000011 
Figure HDA0005101282200000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a method for preparing a solar cell active layer of small molecule doped methylammonium-free perovskite. Background Art
[0002] In recent years, the certified efficiency of perovskite solar cells has rapidly climbed from 3.8% in 2009 to the current 26.7%. It is a strong competitor to solar devices based on traditional photovoltaic materials such as copper indium gallium selenide, gallium arsenide, crystalline silicon and polycrystalline silicon, and has therefore attracted widespread attention. Compared with traditional materials, perovskite formulas are flexible and can change multiple properties such as band gap width and phase transition temperature by adjusting the components, and at the same time have an extremely high absorption coefficient (>104cm-1). Perovskite materials with a thickness of about 500nm can complete the absorption and conversion of sunlight, and the processing temperature of perovskite materials is relatively low (100℃~300℃), so it has attracted close attention from researchers.
[0003] However, the theoretical limit efficiency of perovskite solar cells can reach about 33%, which is still a big gap from the actual efficiency. The main reason for this result is that there are a large number of non-intrinsic defects at the interface and grain boundary of the perovskite film. Taking polycrystalline MAPbI3 as an example, its surface defect density is about 1016~1017cm-3, which is much higher than traditional photovoltaic semiconductor materials such as single crystal silicon (109~1010cm-3), polycrystalline silicon (1014cm-3) and copper indium gallium selenide (1013cm-3). In addition, there are also a large number of defects such as hydroxyl groups and oxygen vacancies on the surface of the metal oxide carrier transport layer materials commonly used in perovskite cells, which hinder carrier extraction and cause serious energy. Therefore, it is urgent to use interface engineering to modify the interface between the perovskite / metal oxide layer, thereby suppressing the non-radiative conformity of photogenerated carriers. This is crucial to improving the working efficiency and stability of solar cells. Summary of the invention
[0004] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a perovskite active layer comprises a perovskite film and an organic molecule modification layer, wherein the organic molecule modification layer comprises a-oxopropionic acid.
[0005] Furthermore, the organic molecule modification layer is located on the lower surface of the perovskite film.
[0006] The method for preparing a perovskite active layer is characterized by comprising the following steps:
[0007] Step 1: Dissolve components including formamidinium iodine, lead iodide, and cesium iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; dissolve α-oxopropionic acid in chlorobenzene to obtain an α-oxopropionic acid small molecule solution.
[0008] Step 2: drop a-oxopropionic acid small molecule solution onto the surface of the electron transport layer and spin coat;
[0009] Step 3: Annealing to obtain a small molecule modified layer;
[0010] Step 4: Add the perovskite precursor solution dropwise onto the surface of the ETL / small molecule modified layer film and continue spin coating;
[0011] Step 5: Add the anti-solvent dropwise onto the surface of the perovskite film and continue spin coating;
[0012] Step 6: Annealing to obtain a perovskite active layer.
[0013] Furthermore, in the step 1, the volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide is 1:4;
[0014] The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L;
[0015] In the perovskite precursor solution,
[0016] The dosage of formamidine iodine is 1.15 mol / L to 1.19 mol / L;
[0017] The dosage of cesium iodide is 0.03mol / L~0.023mol / L;
[0018] The dosage of lead iodide is 1.355mol / L~1.375mol / L;
[0019] The dosage of amidinotaurine is 0.02mol / L~0.03mol / L;
[0020] In the α-oxopropionic acid small molecule solution, the amount of α-oxopropionic acid is 2 mg / mL;
[0021] The spin coating speed in step 2 is 2000 rpm to 4000 rpm;
[0022] The annealing conditions in step 3 are as follows: the annealing temperature is 70°C to 130°C, and the annealing time is 5min to 15min;
[0023] The amount of the perovskite precursor solution spin-coated in step 4 is 30-40 μL;
[0024] The spin coating speed in step 4 is 3000 rpm to 5000 rpm;
[0025] The amount of anti-solvent used in step 5 is 60-80 μL;
[0026] The annealing conditions in step 6 are: annealing temperature 80-120°C, annealing time 20-40min;
[0027] The anti-solvent is selected from chlorobenzene or ether.
[0028] Furthermore, the concentration of the perovskite precursor solution is 1.3 mol / L.
[0029] Furthermore, in the perovskite precursor solution, the amount of formamidinium iodide used was 1.17 mol / L.
[0030] Furthermore, in the perovskite precursor solution, the amount of cesium iodide used is 0.013 mol / L.
[0031] Furthermore, in the perovskite precursor solution, the amount of lead iodide used is 1.365 mol / L.
[0032] Furthermore, in the perovskite precursor solution, the amount of amidinotaurine used is 0.026 mol / L.
[0033] Furthermore, the spin coating speed in step 2 is 2500 rpm to 3500 rpm.
[0034] Furthermore, the spin coating speed in step 2 is 3000 rpm.
[0035] Furthermore, the annealing temperature in step three is 80°C to 120°C.
[0036] Furthermore, the annealing temperature in step three is 100°C.
[0037] Furthermore, the annealing treatment time in step three is 8-13 minutes.
[0038] Furthermore, the annealing treatment time in step three is 10 minutes.
[0039] Furthermore, the perovskite precursor solution spin-coated in step 4 is 35 μL
[0040] Furthermore, the spin coating speed in step 4 is 3500 rpm to 4500 rpm.
[0041] Furthermore, the spin coating speed in step 4 is 4000 rpm.
[0042] Furthermore, the amount of anti-solvent used in step 5 is 70 μL
[0043] Furthermore, the annealing conditions in step six are: annealing temperature 100°C.
[0044] Furthermore, the annealing conditions in step six are: the annealing time is 30 minutes.
[0045] Perovskite solar cells include a conductive glass substrate, an electron transport layer, a perovskite film, a hole transport layer, a blocking layer and a metal electrode in sequence.
[0046] Furthermore, the conductive glass substrate is ITO glass;
[0047] The electron transport layer is tin oxide;
[0048] The small molecule modification layer is a-oxopropionic acid;
[0049] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD);
[0050] The barrier layer is molybdenum oxide;
[0051] The metal electrode is gold or silver.
[0052] Furthermore, the metal electrode is silver.
[0053] Further,
[0054] The thickness of the electron transport layer is 1 to 100 nm;
[0055] The thickness of the organic molecule modification layer is not less than 0.2 nm;
[0056] The thickness of the perovskite active layer is not less than 200 nm;
[0057] The thickness of the hole transport layer is 20 to 100 nm;
[0058] The thickness of the buffer layer is 3 to 20 nm;
[0059] The thickness of the metal electrode is 50 to 200 nm;
[0060] Furthermore, the thickness of the electron transport layer is 30-50 nm.
[0061] Furthermore, the thickness of the organic molecule modification layer is not less than 0.5 to 2 nm;
[0062] Furthermore, the thickness of the perovskite film is 300-500 nm.
[0063] Furthermore, the thickness of the hole transport layer is 50-80 nm.
[0064] Furthermore, the thickness of the buffer layer is 5-8 nm.
[0065] Furthermore, the thickness of the metal electrode is 80-100 nm.
[0066] The preparation method of a perovskite solar cell comprises cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite film, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, and is characterized in that it comprises the following steps:
[0067] Step 1: Clean the ITO substrate with a solvent and then dry it;
[0068] Step 2: Preparation of solution:
[0069] (a) Preparation of a perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide, and cesium iodide are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0070] (b) Preparation of a-oxopropionic acid solution: 2 mg of a-oxopropionic acid salt powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain an a-oxopropionic acid solution;
[0071] (C) Preparation of electron transport layer solution:
[0072] A 15 mol / L tin oxide colloidal solvent and deionized water were mixed at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution;
[0073] (D) Preparation of hole transport layer solution:
[0074] Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution;
[0075] Step 3: Preparation of electron transport layer
[0076] In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film;
[0077] Step 4: Preparation of organic molecule modification layer
[0078] In a protective gas atmosphere, the a-oxopropionic acid solution is firstly spin-coated on the perovskite film to start spin coating; annealing treatment is performed to obtain an electron transport layer film modified with small molecules;
[0079] Step 5: Preparation of perovskite active layer
[0080] In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, anti-solvent chlorobenzene is dropped onto the film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer film;
[0081] Step 6: Preparation of hole transport layer
[0082] In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer.
[0083] Step 7, evaporating a barrier layer of molybdenum oxide;
[0084] Step 8: Evaporating metal electrodes.
[0085] Further,
[0086] The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 60-80 μL;
[0087] The a-oxopropionic acid solution is added dropwise in an amount of 40-60 μL each time;
[0088] The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
[0089] Furthermore, the anti-solvent is chlorobenzene or ethyl ether, and the amount added in each spin coating is 70 μL.
[0090] Furthermore, the amount of the α-oxopropionic acid solution added dropwise each time is 50 μL.
[0091] Further,
[0092] The protective gas is selected from nitrogen;
[0093] The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone;
[0094] The spin coating speed in step 3 is 2000 rpm to 5000 rpm;
[0095] The spin coating speed in step 4 is 2000 rpm to 5000 rpm.
[0096] The annealing conditions in step 4 are as follows: the annealing temperature is 80°C to 150°C, and the annealing time is 5min to 15min;
[0097] The annealing conditions in step 5 are: annealing temperature 80°C to 150°C, annealing time 20min to 40min;
[0098] The evaporation conditions of step 57 are as follows: the pressure of the evaporation chamber is maintained below 2×10-6 torr, and the evaporation rate is 0.01 nm / s to 0.02 nm / s;
[0099] The evaporation conditions in step eight are as follows: the pressure in the evaporation chamber is maintained below 2×10-6 torr, and the evaporation rate is 0.5 nm / s to 1 nm / s.
[0100] Furthermore, the spin coating speed in step three is 2500 rpm to 4000 rpm.
[0101] Furthermore, the spin coating speed in step three is 3000 rpm.
[0102] Furthermore, in the step 4, the a-oxopropionic acid solution spin-coated in the step 2) is 50 μL in terms of volume content;
[0103] Furthermore, the spin coating speed in step 4 is 2500 rpm to 3500 rpm.
[0104] Furthermore, the spin coating speed in step 4 is 3000 rpm.
[0105] Furthermore, the annealing conditions in step 4 are as follows: the annealing temperature is 90°C to 120°C.
[0106] Furthermore, the annealing treatment condition in step 4 is: the annealing treatment temperature is 100°C.
[0107] Furthermore, the annealing treatment conditions in step 4 are: the annealing treatment time is 10 minutes.
[0108] Furthermore, the annealing treatment condition in step five is: annealing treatment temperature is 100°C.
[0109] Furthermore, the annealing treatment conditions in step five are: the annealing treatment time is 30 minutes.
[0110] The beneficial effects of the present invention are:
[0111] 1. Introduce an organic molecular layer to modify the interface of the perovskite / metal oxide electron transport layer, reduce the non-radiative recombination loss of photogenerated carriers at the interface, reduce the overall energy loss of the device, and improve the photovoltaic performance of solar cells. The perovskite device prepared in this way has good photoelectric conversion efficiency and atmospheric stability
[0112] 2. The organic small molecule material also contains a large number of unpaired functional groups, which can coordinate with defects such as hydroxyl groups and oxygen vacancies on the surface of the electron transport layer, passivate surface defects, and thus inhibit the non-radiative recombination of photogenerated carriers at the interface between the electron transport layer and the perovskite, reduce the voltage loss at the lower interface of the perovskite device, and effectively improve the carrier extraction efficiency, and ultimately improve the photoelectric efficiency and atmospheric placement stability of the overall device; compared with unmodified devices, the interface defects of the perovskite / electron transport layer prepared by the method proposed in the present invention are effectively passivated, and the transmission efficiency of photogenerated carriers at the interface is significantly improved, thereby improving the corresponding photoelectric conversion efficiency and stability
[0113] 3. This technical solution proposes a strategy of introducing organic small molecule interface engineering modification to improve the interface quality of perovskite / electron transport layer, that is, introducing a-oxopropionic acid organic molecules containing a large number of unpaired functional groups to eliminate defects in the interface of perovskite / electron transport layer and improve the carrier transmission efficiency at the interface.
[0114] 4. The interface preparation method provided by this technical solution is simple to operate; the number of defects in the prepared perovskite / electron transport layer interface is small; the various parameters of the photovoltaic device prepared based on the modified interface are significantly improved, and it has good atmospheric stability.
[0115] 5. This technical solution simplifies the preparation process of perovskite solar cells, and can be made without adding additional hardware equipment. Through a simple strategy to passivate defects, improve the carrier transfer efficiency of the lower interface, and enhance the performance of solar cells. It provides an effective strategy for preparing high-quality perovskite / electron transport layer interfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0116] Figure 1 This is a schematic structural diagram of a perovskite solar cell according to Example 1 of the present invention;
[0117] Figure 2 JV curves of perovskite solar cells modified with and without a-oxopropionic acid;
[0118] Figure 3 The external quantum efficiency (EQE) curves of the battery modified with or without α-oxopropionic acid are shown;
[0119] Figure 4 The integrated current curve of EQE of the perovskite cell without the introduction of a-oxopropionic acid modification;
[0120] Figure 5 The integrated current curve of EQE of the perovskite cell modified with a-oxopropionic acid;
[0121] Figure 6Electrochemical impedance spectroscopy (EIS) of perovskite photovoltaic devices containing a-oxopropionic acid modified layer and unmodified;
[0122] Figure 7 This is a stability test curve of perovskite photovoltaic devices containing an a-oxopropionic acid modified layer and an unmodified layer in atmospheric environment. DETAILED DESCRIPTION
[0123] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0124] See also Figure 1-7 The present invention provides the following technical solution: a perovskite active layer includes a perovskite film and an organic molecule modification layer, wherein the organic molecule modification layer includes a-oxopropionic acid.
[0125] In this embodiment, the organic molecule modification layer is located on the lower surface of the perovskite film.
[0126] The method for preparing a perovskite active layer comprises the following steps:
[0127] Step 1: Dissolve components including formamidinium iodine, lead iodide, and cesium iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; dissolve α-oxopropionic acid in chlorobenzene to obtain an α-oxopropionic acid small molecule solution.
[0128] Step 2: drop a-oxopropionic acid small molecule solution onto the surface of the electron transport layer and spin coat;
[0129] Step 3: Annealing to obtain a small molecule modified layer;
[0130] Step 4: Add the perovskite precursor solution dropwise onto the surface of the ETL / small molecule modified layer film and continue spin coating;
[0131] Step 5: Add the anti-solvent dropwise onto the surface of the perovskite film and continue spin coating;
[0132] Step 6: Annealing to obtain a perovskite active layer.
[0133] In this embodiment,
[0134] Step 1: dissolving components including lead iodide, cesium iodide and iodine iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; dissolving α-oxopropionic acid powder in chlorobenzene to obtain an α-oxopropionic acid small molecule solution;
[0135] Step 2: first spin-coat an α-oxopropionic acid solution on the SnO2 electron transport layer;
[0136] After annealing in step 3, an organic small molecule modification layer is obtained;
[0137] Step 4: drip the perovskite precursor solution onto the small molecule modified layer film and continue spin coating;
[0138] Step 5: dripping the anti-solvent onto the perovskite film and continuing spin coating;
[0139] Step 6) annealing to obtain a perovskite active layer;
[0140] For unmodified perovskite films, just skip steps 2 and 3 and keep the rest unchanged.
[0141] In the above method for preparing the perovskite active layer, in step 1:
[0142] In this embodiment, the volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4;
[0143] The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L;
[0144] In the perovskite precursor solution,
[0145] The dosage of formamidine iodine is 1.15 mol / L to 1.19 mol / L;
[0146] The dosage of cesium iodide is 0.03mol / L~0.023mol / L;
[0147] The dosage of lead iodide is 1.355mol / L~1.375mol / L;
[0148] The dosage of amidinotaurine is 0.02mol / L~0.03mol / L;
[0149] In the α-oxopropionic acid small molecule solution, the amount of α-oxopropionic acid is 2 mg / mL;
[0150] The spin coating speed in step 2 is 2000 rpm to 4000 rpm;
[0151] The annealing conditions in step 3 are as follows: the annealing temperature is 70°C to 130°C, and the annealing time is 5min to 15min;
[0152] The amount of the perovskite precursor solution spin-coated in step 4 is 30-40 μL;
[0153] The spin coating speed in step 4 is 3000 rpm to 5000 rpm;
[0154] The amount of anti-solvent used in step 5 is 60-80 μL;
[0155] The annealing conditions in step 6 are: annealing temperature 80-120°C, annealing time 20-40min;
[0156] The anti-solvent is selected from chlorobenzene or ether.
[0157] In this embodiment, the concentration of the perovskite precursor solution is preferably 1.3 mol / L.
[0158] In this embodiment, preferably, the dosage of formamidinium iodine in the perovskite precursor solution is 1.17 mol / L.
[0159] Preferably, in this embodiment, the amount of cesium iodide in the perovskite precursor solution is 0.013 mol / L.
[0160] Preferably, in this embodiment, the amount of lead iodide in the perovskite precursor solution is 1.365 mol / L.
[0161] In this embodiment, preferably, the amount of amidinotaurine in the perovskite precursor solution is 0.026 mol / L.
[0162] In this embodiment, the spin coating speed in step 2 is preferably 2500 rpm to 3500 rpm.
[0163] In this embodiment, preferably, the spin coating speed in step 2 is 3000 rpm.
[0164] In this embodiment, preferably, the annealing temperature in step three is 80° C. to 120° C.
[0165] In this embodiment, preferably, the annealing temperature in step three is 100°C.
[0166] In this embodiment, preferably, the annealing treatment time in step three is 8-13 minutes.
[0167] Preferably, in the present embodiment, the annealing treatment time in step three is 10 minutes.
[0168] In this embodiment, the spin-coated perovskite precursor solution in step 4 is preferably 35 μL.
[0169] In this embodiment, the spin coating speed in step 4 is preferably 3500 rpm to 4500 rpm.
[0170] Preferably, in this embodiment, the spin coating speed in step 4 is 4000 rpm.
[0171] In this embodiment, the amount of anti-solvent used in step 5 is preferably 70 μL.
[0172] In this embodiment, preferably, the annealing condition in step six is: annealing temperature is 100°C.
[0173] Preferably, in this embodiment, the annealing condition in step six is: the annealing time is 30 minutes.
[0174] Perovskite solar cells include a conductive glass substrate, an electron transport layer, a perovskite film, a hole transport layer, a blocking layer and a metal electrode in sequence.
[0175] Furthermore, the conductive glass substrate is ITO glass;
[0176] The electron transport layer is tin oxide;
[0177] The small molecule modification layer is a-oxopropionic acid;
[0178] The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD);
[0179] The barrier layer is molybdenum oxide;
[0180] The metal electrode is gold or silver.
[0181] Preferably, in this embodiment, the metal electrode is silver.
[0182] In this embodiment,
[0183] The thickness of the electron transport layer is 1 to 100 nm;
[0184] The thickness of the organic molecule modification layer is not less than 0.2 nm;
[0185] The thickness of the perovskite active layer is not less than 200 nm;
[0186] The thickness of the hole transport layer is 20 to 100 nm;
[0187] The thickness of the buffer layer is 3 to 20 nm;
[0188] The thickness of the metal electrode is 50 to 200 nm;
[0189] Preferably, in this embodiment, the thickness of the electron transport layer is 30-50 nm.
[0190] Preferably, in this embodiment, the thickness of the organic molecule modification layer is not less than 0.5 to 2 nm;
[0191] Preferably, in this embodiment, the thickness of the perovskite film is 300-500 nm.
[0192] In this embodiment, preferably, the thickness of the hole transport layer is 50-80 nm.
[0193] Preferably, in this embodiment, the thickness of the buffer layer is 5-8 nm.
[0194] In this embodiment, preferably, the thickness of the hole transport layer is 80-100 nm.
[0195] The preparation method of a perovskite solar cell comprises cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite film, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, and comprises the following steps:
[0196] Step 1: Clean the ITO substrate with a solvent and then dry it;
[0197] Step 2: Preparation of solution:
[0198] (a) Preparation of a perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide, and cesium iodide are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution;
[0199] (b) Preparation of a-oxopropionic acid solution: 2 mg of a-oxopropionic acid salt powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain an a-oxopropionic acid solution;
[0200] (C) Preparation of electron transport layer solution:
[0201] A 15 mol / L tin oxide colloidal solvent and deionized water were mixed at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution;
[0202] (D) Preparation of hole transport layer solution:
[0203] Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution;
[0204] Step 3: Preparation of electron transport layer
[0205] In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film;
[0206] Step 4: Preparation of organic molecule modification layer
[0207] In a protective gas atmosphere, the a-oxopropionic acid solution is firstly spin-coated on the perovskite film to start spin coating; annealing treatment is performed to obtain an electron transport layer film modified with small molecules;
[0208] Step 5: Preparation of perovskite active layer
[0209] In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, anti-solvent chlorobenzene is dropped onto the film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer film;
[0210] Step 6: Preparation of hole transport layer
[0211] In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer.
[0212] Step 7, evaporating a barrier layer of molybdenum oxide;
[0213] Step 8: Evaporating metal electrodes.
[0214] In the above steps, the specific operation of cleaning the ITO substrate in step 1 is: ultrasonic cleaning is performed once with anhydrous isopropanol, deionized water, deionized water, deionized water and anhydrous isopropanol, each for 30 minutes; and then dried in a drying oven. Before use, the cleaned ITO glass needs to be treated with vacuum ultraviolet ozone (UV-Ozone). Ultraviolet ozone surface treatment can be achieved using equipment and processing conditions commonly used in the art, for example: UV-Ozone power is 200W, and the processing time is 3min.
[0215] In the step (a):
[0216] The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide is 1:4. In terms of molar percentage, the concentration of the perovskite precursor solution is 1.3 mol / L;
[0217] In the perovskite precursor solution, the amount of formamidine iodine is 1.17 mol / L, the amount of cesium iodide is 0.13 mol / L, and the amount of lead iodide is 1.365 mol / L;
[0218] In the α-oxopropionic acid small molecule solution, the concentration of the α-oxopropionic acid solution is 2 mg / mL;
[0219] According to an embodiment of the present invention, in the step (b): 15 mol / L of tin oxide colloidal solvent is mixed and diluted with deionized water in a volume ratio of 1:3 to obtain a tin oxide colloidal solvent.
[0220] According to an embodiment of the present invention, in the step (c): 72 mg of spiro-OMeTAD is dissolved in 1 mL of an organic solvent, chlorobenzene, to obtain a hole transport layer solution.
[0221] In the step (a):
[0222] The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide is 1:4. In terms of molar percentage, the concentration of the perovskite precursor solution is 1.3 mol / L;
[0223] In the perovskite precursor solution, the amount of formamidine iodine is 1.17 mol / L, the amount of cesium iodide is 0.13 mol / L, and the amount of lead iodide is 1.365 mol / L;
[0224] In the α-oxopropionic acid small molecule solution, the concentration of the α-oxopropionic acid solution is 2 mg / mL;
[0225] In the step (b):
[0226] The tin oxide colloidal solvent of 15 mol / L is mixed and diluted with deionized water in a volume ratio of 1:3 to obtain the solution.
[0227] In the step (c):
[0228] 72 mg of spiro-OMeTAD was dissolved in 1 mL of organic solvent chlorobenzene to obtain a hole transport layer solution.
[0229] In this embodiment,
[0230] The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 60-80 μL;
[0231] The a-oxopropionic acid solution is added dropwise in an amount of 40-60 μL each time;
[0232] The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
[0233] In this embodiment, the anti-solvent is preferably chlorobenzene or ethyl ether, and the amount added during each spin coating is 70 μL.
[0234] In this embodiment, the preferred amount of the α-oxopropionic acid solution added dropwise each time is 50 μL.
[0235] In this embodiment,
[0236] The protective gas is selected from nitrogen;
[0237] The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone;
[0238] The spin coating speed in step 3 is 2000 rpm to 5000 rpm;
[0239] The spin coating speed in step 4 is 2000 rpm to 5000 rpm.
[0240] The annealing conditions in step 4 are as follows: the annealing temperature is 80°C to 150°C, and the annealing time is 5min to 15min;
[0241] The evaporation conditions of step 57 are as follows: the pressure of the evaporation chamber is maintained below 2×10-6 torr, and the evaporation rate is 0.01 nm / s to 0.02 nm / s;
[0242] The evaporation conditions in step eight are as follows: the pressure in the evaporation chamber is maintained below 2×10-6 torr, and the evaporation rate is 0.5 nm / s to 1 nm / s.
[0243] Preferably, in this embodiment, the spin coating speed in step three is 2500 rpm to 4000 rpm.
[0244] Preferably, in this embodiment, the spin coating speed in step three is 3000 rpm.
[0245] Preferably, in the step 4, the a-oxopropionic acid solution spin-coated in the step 2) is 50 μL in terms of volume content;
[0246] Preferably, in this embodiment, the spin coating speed in step 4 is 2500 rpm to 3500 rpm.
[0247] Preferably, in this embodiment, the spin coating speed in step 4 is 3000 rpm.
[0248] In this embodiment, preferably, the annealing condition in step 4 is: the annealing temperature is 90° C. to 120° C.
[0249] In this embodiment, the annealing condition in step 4 is preferably: the annealing temperature is 100°C.
[0250] Preferably, in the present embodiment, the annealing treatment condition in step 4 is: the annealing treatment time is 10 minutes.
[0251] In this embodiment, preferably, the annealing condition in step five is: annealing temperature is 100°C.
[0252] Preferably, in this embodiment, the annealing condition in step five is: the annealing time is 30 minutes.
[0253] The test instruments and test conditions used in the examples are as follows:
[0254] JV curve: First, the light intensity of the solar simulator system is calibrated by the silicon photodiode and KG5 filter calibrated by the US Renewable Energy Laboratory. Then, the device is placed under the calibrated test light source using a test fixture (performed in an N2 glove box), and the JV characteristic curve of the perovskite semiconductor optoelectronic device is automatically tested by the Keithley source meter and the corresponding configured software, and the open-circuit voltage (V) is obtained from the curve. oc ), short-circuit current density (Short-circuit density, J sc ), fill factor (FF) and power conversion efficiency (PCE).
[0255] During the JV curve test, the test voltage was set to -0.2V to 1.4V, the interval was 0.02V, and the delay time was 0.1s.
[0256] EQE measurements were performed using a commercial quantum efficiency measurement system (QE-R, Enlitech) equipped with a xenon lamp light source and an elliptical collector.
[0257] Electrochemical impedance spectroscopy (EIS) tests were performed based on a commercially available PIAOs testing system (Fluxim4.0).
[0258] Unless otherwise stated, all solvents and materials used in the examples were obtained from commercial sources and used without further purification.
[0259] The ITO transparent electrode glass (10Ωsq -1 ) was purchased from Youxuan Technology Co., Ltd.
[0260] Cesium iodide (CsI, purity 99.999%), molybdenum oxide (MoO3, purity 99.97%), chlorobenzene (CB, purity 99.8%) were purchased from Sigma-Aldrich. Formamidinium iodide (FAI, purity ≥ 99.5%) and spiro-OMeTAD (purity ≥ 99.5%) were purchased from Xi'an Biolight Optoelectronics Technology Co., Ltd. a-Oxopropionic acid (purity ≥ 98%) was purchased from Aladdin. PbI2 (purity 99.99%) was purchased from Tokyo Chemical Industry. DMSO (purity 99.9%) and DMF (purity ≥ 99%) were purchased from Acros Organics. SnO2 colloidal dispersion was purchased from Alfa Aesar.
[0261] a-Oxopropionic acid modification group
[0262] The device structure of the perovskite solar cell in this modification group is: ITO / SnO2 / Perovskite / spiro-OMeTAD / MoO3 / Ag, such as Figure 1 shown.
[0263] The specific preparation process is as follows:
[0264] Prepare perovskite precursor solution:
[0265] Prepare FA with a concentration of 1.3 mol / L 0.9 Cs 0.1 PbI3 perovskite solution: 629.2 mg of lead iodide (PbI2), 206.1 mg of iodomethane (FAI), and 33.8 mg of cesium iodide (CsI) were mixed and dissolved in 1 mL of a mixed solvent of DMF and DMSO. The volume ratio of deuterated dimethyl sulfoxide to dimethylformamide was 1:4. The prepared solution was placed on a constant temperature magnetic stirrer and stirred for more than 24 hours, and stored in a nitrogen glove box for later use.
[0266] Preparation of a-oxopropionic acid small molecule solution:
[0267] 2 mg of a-oxopropionic acid powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain a 1-phenylbiguanide hydrochloride solution.
[0268] Prepare electron transport layer solution:
[0269] A 15 mol / L tin oxide colloidal solvent was mixed with deionized water at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution.
[0270] Preparation of perovskite solar cells (the experimental group and the control group have the same steps):
[0271] The ITO glass was ultrasonically cleaned in anhydrous isopropanol, deionized water, deionized water, deionized water and anhydrous isopropanol in turn, each for 30 minutes; then dried in a drying oven. Before using the cleaned ITO glass, its surface needs to be treated with vacuum ultraviolet ozone (UV-Ozone) for 3 minutes to improve wettability.
[0272] Spin coat the SnO2 colloidal dispersion to obtain the SnO2 layer at a speed of 4000 rpm for 30 seconds. Anneal the prepared glass / ITO / SnO2 on a 150°C hot plate for 20 minutes to promote complete evaporation of the solvent. After the annealing is completed and the substrate layer is cooled to room temperature, it is transferred to a nitrogen environment glove box, and the prepared a-oxopropionic acid small molecule solution is drop-coated on the cooled SnO2 surface at a speed of 3000 rpm for 30 seconds, then removed and quickly placed on a 100°C hot plate for annealing for 10 minutes. Then spin coat the perovskite precursor solution to obtain the perovskite film at a speed of 4000 rpm for 35 seconds. 8 seconds before the end of the spin coating, quickly drop 70 μL of chlorobenzene solution on the surface of the perovskite film. After the spin coating is completed, remove it and quickly place it on a 150°C hot plate for annealing for 20 minutes. Then the prepared spiro-OMeTAD was spin-coated on the perovskite layer at a speed of 4000 rpm for 20 seconds. Finally, the film was transferred to a high vacuum evaporation device and the vacuum was 2×10 -6 In a torr environment, MoO3 with a thickness of 7nm and Ag with a thickness of 100nm were sequentially evaporated.
[0273] For the unmodified group, i.e., the control group, there was no need to spin-coat the a-oxopropionic acid small molecule solution, and the remaining steps were the same.
[0274] Current density voltage (JV) test
[0275] The current density voltage (JV) curve of the perovskite solar cells in the experimental group with a-oxopropionic acid added and the control group without a-oxopropionic acid added was tested. The results are shown in Figure 2 and Table 1.
[0276] Table 1. Photovoltaic parameters of devices in the experimental group and the control group
[0277]
[0278] from Figure 2 As can be seen from Table 1, the short-circuit current density of the device with the introduction of a-oxopropionic acid small molecule modification layer increased from 23.58 to 24.00 mA / cm 2, the open circuit voltage increased from 1.162 to 1.195V, and the fill factor increased from 78.0% to 78.5%. This result shows that the modification of the perovskite / electron transport layer interface by the a-oxopropionic acid molecular layer can passivate the deep energy level defects at the interface, reduce the non-radiative recombination of carriers at the interface, and improve the extraction efficiency. Finally, the photoelectric conversion efficiency of the perovskite solar cell increased from 21.37% to 22.53%.
[0279] according to Figure 2 It can be seen that the open circuit voltage (V OC ) and short-circuit current (J SC ) is significantly improved, and the fill factor (FF) is slightly improved. OC The improvement may be due to the lower energy loss in the device. SC The improvement may be due to the improvement of carrier extraction efficiency in the device. Finally, the photoelectric conversion efficiency of the device was significantly improved after modification with the α-oxopropionic acid molecular layer.
[0280] according to Figure 3 It can be seen that the EQE efficiency of the device modified with a-oxopropionic acid in the 300nm to 400nm band is significantly improved, indicating that the carrier extraction efficiency at the perovskite / electron transport layer interface in the modified device may be improved, thereby improving the transmission efficiency of photogenerated carriers at 300nm to 400nm.
[0281] according to Figure 4 It can be seen that the integrated current of the device is 23.05mA / cm2, which is consistent with the result of the JV test.
[0282] according to Figure 5 It can be seen that the integrated current of the device is 23.45mA / cm2, which is consistent with the result of the JV test.
[0283] Figure 6 It reflects the transport and recombination characteristics of carriers. The figure can be divided into low-frequency and high-frequency regions, which can respectively reflect the carrier recombination characteristics and carrier transport characteristics inside the device. By comparison, it can be seen that the conformal impedance of the device modified with the a-oxopropionic acid molecular layer is much greater than that of the unmodified device, indicating that the passivation effect of the a-oxopropionic acid molecules at the interface of the former significantly reduces the defect density at the interface, thereby inhibiting the non-radiative recombination of photogenerated carriers at the interface of the perovskite / electron transport layer and improving the carrier extraction efficiency. This result is consistent with the test results of EQE.
[0284] Figure 7The test environment temperature was about 25°C and the humidity was about 40%. By comparison, it can be seen that the device modified with the a-oxopropionic acid molecular layer can still maintain about 80% of the initial efficiency after 30 days of storage. On the 12th day, the efficiency of the unmodified device dropped to about 35% of the initial efficiency. This result shows that the device modified with a-oxopropionic acid has stronger resistance to water, oxygen, etc. in the atmosphere, and therefore has better stability. This may be because the a-oxopropionic acid modification layer improves the surface morphology of SnO2, provides better conditions for the crystallization process of the perovskite film, and thus improves the quality of the film.
[0285] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A perovskite active layer, comprising a perovskite film and an organic molecule modified layer, characterized in that: The organic molecule modification layer includes α-oxopropionic acid.
2. The perovskite active layer according to claim 1, characterized in that: The organic molecule modification layer is located on the lower surface of the perovskite film.
3. A method for preparing a perovskite active layer, characterized in that: The following steps are involved: Step 1: Dissolve components including formamidinium iodine, lead iodide, and cesium iodide in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; dissolve α-oxopropionic acid in chlorobenzene to obtain an α-oxopropionic acid small molecule solution. Step 2: drop a-oxopropionic acid small molecule solution onto the surface of the electron transport layer and spin coat; Step 3: Annealing to obtain a small molecule modified layer; Step 4: Add the perovskite precursor solution dropwise onto the surface of the ETL / small molecule modified layer film and continue spin coating; Step 5: Add the anti-solvent dropwise onto the surface of the perovskite film and continue spin coating; Step 6: Annealing to obtain a perovskite active layer.
4. The method for preparing a perovskite active layer according to claim 1, characterized in that: The volume ratio of the mixed solution of deuterated dimethyl sulfoxide and dimethylformamide in step 1 is 1:4; The concentration of the perovskite precursor solution is 1.25 mol / L to 1.35 mol / L; In the perovskite precursor solution, The dosage of formamidine iodine is 1.15 mol / L to 1.19 mol / L; The dosage of cesium iodide is 0.03mol / L~0.023mol / L; The dosage of lead iodide is 1.355mol / L~1.375mol / L; The dosage of amidinotaurine is 0.02mol / L~0.03mol / L; In the α-oxopropionic acid small molecule solution, the amount of α-oxopropionic acid is 2 mg / mL; The spin coating speed in step 2 is 2000 rpm to 4000 rpm; The annealing conditions in step 3 are as follows: the annealing temperature is 100° C. to 200° C., and the annealing time is 5 min to 15 min; The amount of the perovskite precursor solution spin-coated in step 4 is 30-40 μL; The spin coating speed in step 4 is 3000 rpm to 5000 rpm; The amount of anti-solvent used in step 5 is 60-80 μL; The annealing conditions in step 6 are: annealing temperature 80-120°C, annealing time 20-40min; The anti-solvent is selected from chlorobenzene or ether.
5. A perovskite solar cell, characterized in that: The method comprises, in sequence, a conductive glass substrate, an electron transport layer, a perovskite active layer according to any one of claims 1 to 2 or a perovskite active layer prepared by any one of claims 3 to 5, a hole transport layer, a barrier layer and a metal electrode.
6. The perovskite solar cell according to claim 5, characterized in that: The conductive glass substrate is ITO glass; The electron transport layer is tin oxide; The small molecule modification layer is a-oxopropionic acid; The hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD); The barrier layer is molybdenum oxide; The metal electrode is gold or silver.
7. The perovskite solar cell according to claim 6, characterized in that: The thickness of the electron transport layer is 1 to 100 nm; The thickness of the organic molecule modification layer is not less than 0.2 nm; The thickness of the perovskite active layer is not less than 200 nm; The thickness of the hole transport layer is 20 to 100 nm; The thickness of the buffer layer is 3 to 20 nm; The thickness of the metal electrode is 50-200 nm.
8. A method for preparing a perovskite solar cell, comprising cleaning the surface of a conductive glass substrate, spin coating an electron transport layer, spin coating a perovskite film, spin coating a hole transport layer, evaporating a buffer layer, and evaporating a metal electrode, characterized in that: The following steps are involved: Step 1: Clean the ITO substrate with a solvent and then dry it; Step 2: Preparation of solution: (a) Preparation of perovskite precursor solution: In a protective gas atmosphere, lead halide, amine halide and cesium iodide are dissolved in a mixed solution of deuterated dimethyl sulfoxide and dimethylformamide to obtain a perovskite precursor solution; (b) Preparation of a-oxopropionic acid solution: 2 mg of α-oxopropionate powder was thoroughly mixed with 1 mL of chlorobenzene solvent to obtain an α-oxopropionic acid solution; (C) Preparation of electron transport layer solution: A 15 mol / L tin oxide colloidal solvent and deionized water were mixed at a volume ratio of 1:3 to obtain a diluted tin oxide colloidal solution; (D) Preparation of hole transport layer solution: Dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) in an organic solvent, chlorobenzene, to obtain a hole transport layer solution; Step 3: Preparation of electron transport layer In a protective gas atmosphere, the electron transport layer solution was spin-coated on the ITO substrate and annealed at 150°C for 20 min to obtain an ITO / ETL film; Step 4: Preparation of organic molecule modification layer In a protective gas atmosphere, the a-oxopropionic acid solution is firstly spin-coated on the perovskite film to start spin coating; annealing treatment is performed to obtain an electron transport layer film modified with small molecules; Step 5: Preparation of perovskite active layer In a protective gas atmosphere, the perovskite precursor solution is first spin-coated on the ITO / ETL film to start spin coating; then, 7 seconds before the end of spin coating, anti-solvent chlorobenzene is dropped onto the film to continue spin coating; finally, annealing treatment is performed to obtain the perovskite active layer film; Step 6: Preparation of hole transport layer In a protective gas atmosphere, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) was spin-coated on the perovskite active layer. Step 7, evaporating a barrier layer of molybdenum oxide; Step 8: Evaporating metal electrodes.
9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The anti-solvent is chlorobenzene or ether, and the amount added in each spin coating is 60-80 μL; The a-oxopropionic acid solution is added dropwise in an amount of 40-60 μL each time; The usage ratio of chlorobenzene solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is 1 ml / 72 mg.
10. The method for preparing a perovskite solar cell according to claim 9, characterized in that: The protective gas is selected from nitrogen; The ITO substrate dried in the step 1 is treated with vacuum ultraviolet ozone; The spin coating speed in step 3 is 2000 rpm to 5000 rpm; The spin coating speed in step 4 is 2000 rpm to 5000 rpm; The annealing conditions in step 4 are as follows: the annealing temperature is 100°C to 200°C, and the annealing time is 5min to 15min; In the step 5, the spin-coated perovskite precursor solution is 35 μL in terms of volume content; The spin coating speed in step 5 is 4000 rpm; The annealing conditions in step 5 are: annealing temperature 80°C to 150°C, annealing time 20min to 40min; The evaporation conditions of step 57 are as follows: the pressure of the evaporation chamber is maintained below 2×10-6 torr, and the evaporation rate is 0.01 nm / s to 0.02 nm / s; The evaporation conditions in step eight are as follows: the pressure in the evaporation chamber is maintained below 2×10-6 torr, and the evaporation rate is 0.5 nm / s to 1 nm / s.